2014
DOI: 10.1002/pc.23075
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on phosphorus halogen‐free flame‐retardancy systems in short glass fiber‐reinforced PC/ABS composites under rapid thermal cycle molding process condition

Abstract: In this study, standard test specimens with flameretarded short glass fiber-reinforced PC/ABS materials were fabricated under rapid thermal cycle injection molding condition by selecting a potassium perfluorobutane sulfonate flame retardant specially used for PC, FR2025, and two kinds of aryl phosphorus halogen-free flame retardants, UN707 and PX-220. The flame-retardancy effect of the above different flame retardants on the studied systems was compared through combustion tests of the specimens. Meanwhile, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…E ’ at 30 °C of r‐PC/r‐ABS/FR blends are higher than E ’ of r‐PC/r‐ABS blend (Table ), suggesting a reinforcing effect of the FRs BDP, TPP, and OPE at this temperature, which is characteristic of better compatibility and miscibility of phases ascribed to improved interactions between constituents of blends. Such an effect was already reported for virgin PC/ABS blends with 10 wt % of aryl phosphates, phosphorus‐containing POSS/PC composites, and short glass fiber‐reinforced PC/ABS composites with phosphorus‐based FRs …”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…E ’ at 30 °C of r‐PC/r‐ABS/FR blends are higher than E ’ of r‐PC/r‐ABS blend (Table ), suggesting a reinforcing effect of the FRs BDP, TPP, and OPE at this temperature, which is characteristic of better compatibility and miscibility of phases ascribed to improved interactions between constituents of blends. Such an effect was already reported for virgin PC/ABS blends with 10 wt % of aryl phosphates, phosphorus‐containing POSS/PC composites, and short glass fiber‐reinforced PC/ABS composites with phosphorus‐based FRs …”
Section: Resultssupporting
confidence: 75%
“…Wang et al . reported that the addition of FRs reduced the impact strength of a virgin short glass fiber‐reinforced PC/ABS blend although the SAN phase in ABS contributed to the impact strength of PC/ABS, but the compatibility of FRs and SAN was poor . In our case, the addition of 5 wt % MBS to r‐PC/r‐ABS highly improved impact strength and the test specimens did not break.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Studies have shown that, by using the RHCM process to eliminate weld lines, the surface roughness of molded parts can be significantly reduced. As a result, processes such as spraying and coating can be eliminated, reducing energy, material, and production costs while also protecting the environment [ 55 , 56 , 57 , 58 ]. Thus, it is being considered as a possible manufacturing technology in the plastic injection molding industry.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Khan et al 11 investigated the rheological and mechanical properties of the PC/ABS blends so as to develop alloys comprising as much recycled plastics as manufacturable. Wang et al 12 evaluated the flame-retardant effect of the various flame retardants and fibers in the short glass fiberreinforced PC/ABS composites. The mechanical behavior of PC/ABS blends was also studied experimentally during monotonic and cyclic loading by Wang et al 13 Wegrzyn et al 14 reported the quality of morphology and mechanical behavior of PC/ABSmultiwalled carbon nanotube (MWCNT) nanocomposites with different volume fractions of carbon nanotubes manufactured at different injection velocities.…”
Section: Introductionmentioning
confidence: 99%